Osteolipoma of leg masquerading as Osteoid osteoma: a case report - Shukla, Anurag; Naqvi, Fatema Shareh; Shukla, Anju (Indian Journal of Case Reports, 2024)
Lipomas are the most common, subcutaneous, and slow-growing tumors composed of fat (adipose tissue). Out of many types of these benign tumors, ossifying lipoma (osteolipoma) is the rarest subtype. Here, randomly distributed trabeculae of lamellar bone are seen within mature adipose tissue. They are featured only as isolated case reports and small case series, thus the true incidence is not known. The most common site for osteolipoma is the head and neck region and they are rarely reported in the lower extremities. Herein, we discuss the case of a 19-year-old man who presented with a progressively enlarging painful mass in the left leg. Radiology was typical of osteoid osteoma. Excision was performed and histopathological examination confirmed the lesion as osteolipoma with no evidence of malignancy. No recurrence of the tumor was observed after 2 years of follow-up. Although osteolipoma is a rare entity, the differential diagnosis of the lesion can be kept in mind whenever we encounter ossification within the adipose tissue.